PERKEMBANGAN TATA KOTA SURABAYA PADA TAHUN 1870-1940 - Muhammad Lingga Andana; Izza Yuspriana Afhimma; Silvia Nurul Ashiva (Historiography: Journal of Indonesian History and Education, 2021)
The city of Surabaya became one of the areas that attracted the interest of Europeans to perpetuate power and establish government as well as establish economic relations, especially trade with indigenous peoples. The city of Surabaya has been given the authority to regulate its territory, thus giving rise to the term Gemeente. This article aims to explain how Surabaya’s urban planning has changed across centuries, from 1870-1940. The method used in this article is the study of literature and historical methods. The development of the Surabaya City layout was motivated by the passing of the agrarian and the sugar law. As a result, many people from various ethnic migrated to Surabaya and formed settlements. In addition, another impact is the renewal of Surabaya City infrastructures such as railroads, markets, and highwaysKota Surabaya menjadi salah satu wilayah yang menarik minat orang Eropa untuk melanggengkan kekuasaan dan mendirikan pemerintahan serta menjalin hubungan ekonomi khususnya perdagangan dengan masyarakat pribumi. Kota Surabaya telah diberi kewenangan untuk mengatur wilayahnya sendiri hingga memunculkan istilah Gemeente. Artikel ini bertujuan dalam menjelaskan bagaimana tata Kota Surabaya berubah secara lintas abad, yaitu dari tahun 1870-1940. Metode yang digunakan dalam artikel ini adalah studi kepustakaan serta metode sejarah. Perkembangan tata Kota Surabaya dilatarbelakangi oleh disahkannya undang-undang agraria serta undang-undang gula. Dampaknya banyak penduduk dari berbagai etnis yang bermigrasi ke Kota Surabaya serta membentuk pemukiman-pemukiman. Selain itu dampak lain adalah adanya pembaruan infrastruktur Kota Surabaya seperti rel kereta api, pasar, dan Jalan raya.